14PModulation of pancreatic cancer cell sensitivity to FOLFIRINOX through microRNA-mediated regulation of response to DNA damage. (7th November 2019) - Lampis, A; Carotenuto, P; Hedayat, S; Previdi, M C; Zito, D; Sclafani, F; Parisi, C; Hahne, J C; Hallsworth, A; Kirkin, V; Young, K; Kouvelakis, K; et al.
Abstract: Background: FOLFIRINOX-regime is a combination-chemotherapy that provides the best clinical benefit in pancreatic ductal adenocarcinoma (PDAC) patients, but is associated with severe toxicity. Aim of this study is to explore the role of miRNAs as modulators of chemosensitivity and their potential as biomarkers of sensitivity to FOLFIRINOX-therapy. Methods: HTS of 997 LNA-MIR-inhibitors was performed in PDAC cell lines treated with a combination of Fluorouracil (F), Oxaliplatin (O) and Irinotecan (I) that mimics FOLFIRINOX-regime. Validation experiments were performed with miRvana probes. Apoptosis was measured by flow-cytometry and western-blotting. Knock-out of microRNA was achieved by CRISPR-CAS9 in MiaPaca2 cells. HITS-CLIP assay was used to identify MIR1307 target site. Drug sensitivity was tested in xenograft models. Plasma MIR1307 was assessed by ddPCR. Results: 41 and 84 miRNA-inhibitors enhanced FOI activity by > 30% (p < 0.001) in Capan1 and MiaPaCa2. These included MIR1307-inhibitor that was validated in 6 PDAC cell lines. The effect of FOI in comparison to DMSO was greater in cells transfected with MIR1307 inhibitor vs control, making the effect of this MIR specific for chemotherapy. MIR1307 was over-expressed in tumours of 40/60 human PC cases, confirming clinical relevance. DNA damage markers were upregulated (pH2AX2, 8OHdG, DNA breaks) in KO cells treated with FOI and therapy-induced apoptosis was higher in KO cells. Re-expression of MIR1307 in KO cells increased resistance to FOI chemotherapy and protected from FOI-induced DNA damage. HITS-CLIP assay identified binding of MIR1307 to CLIC5, whose expression was increased in KO cells and reduced by rescued expression of MIR1307. Both WT and KO xenografts responded to FOI chemotherapy but response was transient in WT mice, while we noticed a prolonged response in KO tumours. Baseline plasma level of MIR1307 correlated with overall survival in patients receiving FOLFIRINOX chemotherapy. Conclusions: We identified MIR1307 as a potential modulator of sensitivity to FOI-chemotherapy in PC. MIR1307 inhibition impairs the ability of the cells to recover from chemotherapy damage and therefore enhances its activity. Legal entity responsible for the study: The authors. Funding: Pancreatic Cancer UK Research Innovation Fund, Cancer Research UK. Disclosure: All authors have declared no conflicts of interest.